Repeat Neuroimaging of Mild Traumatic Brain‐injured Patients With Acute Traumatic Intracranial Hemorrhage: Clinical Outcomes and Radiographic Features. (October 2014) - Kreitzer, Natalie; Lyons, Michael S.; Hart, Kim; Lindsell, Cristopher J.; Chung, Sora; Yick, Andrew; Bonomo, Jordan; Goldstein, Joshua N.
Abstract Objectives Emergency department (ED) management of mild traumatic brain injury (TBI) patients with any form of traumatic intracranial hemorrhage (ICH) is variable. Since 2000, our center's standard practice has been to obtain a repeat head computed tomography (CT) at least 6 hours after initial imaging. Patients are eligible for discharge if clinical and CT findings are stable. Whether this practice is safe is unknown. This study characterized clinical outcomes in mild TBI patients with acute traumatic ICH seen on initial ED neuroimaging. Methods This retrospective cohort study included patients presenting to the ED with blunt mild TBI with Glasgow Coma Scale (GCS) scores of 14 or 15 and stable vital signs, during the period from January 2001 to January 2010. Patients with any ICH on initial head CT and repeat head CT within 24 hours were eligible. Cases were excluded for initial GCS < 14, injury > 24 hours old, pregnancy, concomitant nonminor injuries, and coagulopathy. A single investigator abstracted data from records using a standardized case report form and data dictionary. Primary endpoints included death, neurosurgical procedures, and for discharged patients, return to the ED within 7 days. Differences in proportions were computed with 95% confidence intervals (CIs). Results Of 1, 011 patients who presented to the ED and had two head CTs within 24 hours, 323 (32%) met inclusion criteria. The median time between CT scans was 6 hours (interquartile range = 5 to 7 hours). A total of 153 (47%) patients had subarachnoid hemorrhage, 132 (41%) patients had subdural hemorrhage, 11 (3%) patients had epidural hemorrhage, 78 (24%) patients had cerebral contusions, and 59 (18%) patients had intraparenchymal hemorrhage. Four of 323 (1.2%, 95% CI = 0.3% to 3.2%) patients died within 2 weeks of injury. Three of the patients who died had been admitted from the ED on their initial visits, and one had been discharged home. There were 206 patients (64%) discharged from the ED, 28 (13.6%) of whom returned to the ED within 1 week. Of the 92 who were hospitalized, three (0.9%, 95% CI = 0.2% to 2.7%) required neurosurgical intervention. Conclusion Discharge after a repeat head CT and brief period of observation in the ED allowed early discharge of a cohort of mild TBI patients with traumatic ICH without delayed adverse outcomes. Whether this justifies the cost and radiation exposure involved with this pattern of practice requires further study.